(Eugenia polyantha wight)(Study on the effect of distilation condition and withering Time on the Yield and Characterisyics of “Salam” Leaf Oil (Eugenia polyantha Wight) - H. Guring Pohan; Eko Susanto (Warta Industri Hasil Pertanian, 1995)
Salam (Eugenia Polyantha Wight)is a kind of spices which is commonly used in house hold as a food additive.The leaf contains essencial oil which has specific flavour and can be produced by distillation. In this experiment distillation was done by using salt solution with concentration of 0%,1%,2%,3%,5% and 10%.Distillation was carried out for 12 hours from the first drop of distillated water.Distilation was stopped when there was no more of yield increase.The treatment was then continued by distilation of withered leaf of 0,3 and 5 days.The effect of whitering time showed that 5 daysgave the highest yield about 0,17% (dry basis).The result show that the yield  increase with increasing the distillation time and the increase of salt concentration up to optimum (2%) then decrease again.The oil is then calculated and analysed its physic and chemist characteristics.The characteristics of the Eugenia polyantha wight oil has positive optical rotation while bay oil has negative optical rotation.Therefore, "salam oil"is difference with bay oil.